Multi modular toxicity assessment of nephrotoxicity in podophyllotoxin exposure rats on account of toxicological evidence chain (TEC) concept - Kong, Jiao; He, Tao; Liu, Chuanxin; Huang, Jianmei (Ecotoxicology and environmental safety, 2022)
Early diagnosis of kidney injuries caused by herbs is necessary to enable effective treatments, prevent kidney failure and promote the internationalization and modernization of herbal medicine. Whereas the toxic assessment evidence has not integrated yet, and the evaluation method has not been unanimously agreed. For example, the gold standard assessing toxicity in animals remains to be histopathology, but serum biochemical indexes are the primary measures for monitoring organs dysfunction in humans. In this study, using Sprague Dawley rats, we investigated whether integrated analyses of transcriptomic and metabolomic data with toxicological evidence chain (TEC) concept could identify indicators of injury and provide new insights into the mechanisms of nephrotoxicity. Firstly, the objective phenotype of the animals was observed in detail and the toxicity performance was collected after administration. Subsequently, histopathological examination and serum biochemical toxicity evidence were collected. Next, we obtained concurrent measurements of transcriptomic changes in kidneys, and changes along with metabolic profiles in serum, after exposure to PT(Podophyllotoxin) to acquire evidence at the molecular level. Last but not least, the GTEA (Grades of Toxicological Evidence Assessment) based on GRADE(Grading of Recommendations Assessment, Development, and Evaluation) system was used to evaluate toxic evidence which can be assigned to a toxic level. The orally gavaged rats with PT have been confirmed with dose-dependent kidney damage from 5 to 15 mg/kg after 4 d. Our findings suggest that the main pathological changes occurred in Glycerophosphatidylcholine metabolism, Arachidonic acid metabolism, Energy metabolism, Tyrosine metabolism, Tryptophan metabolism and so on.Moreover, the alteration of the potential metabolites lipid (i.e. LPC, palmitic acid) and sulfate could serve as plausible markers of PT-induced kidney injury. Our approach provides a mechanistic framework for the refinement of the grading standard of toxicity evidence, which is applicable to other toxicants originated from herbal medicine based on multi-omics data. •The significant mechanism of nephrotoxicity induced by podophyllotoxin was laid on oxidative stress, Inflammatory effects, Energy metabolism consumption, Immune disorder.•The toxic evidence quality can be assessed as three levels with GTEA (Grades of Toxicological Evidence Assessment).•The toxicological evidence chain (TEC) concept applied for the whole process of toxic evaluation was first optimized with four elements and three principles.